2021
DOI: 10.1108/mbe-12-2020-0161
|View full text |Cite
|
Sign up to set email alerts
|

The impact of digital technologies on business models. Insights from the space industry

Abstract: Purpose In the past decade, in the space industry, many initiatives intended at offering open access to big data from space multiplied. Therefore, firms started adopting business models (BMs) which lever on digital technologies (e.g. cloud computing, high-performance computing and artificial intelligence), to seize these opportunities. Within this scenario, this article aims at answering the following research question: which digital technologies do impact which components the BM is made of? Design/methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
0
8
0
1
Order By: Relevance
“…Zamani et al (2022) mentioned that the appropriate applications of information technology provide guarantees in achieving the goals that have been set. The results of the study showed that technology is compatible with today's developing business concepts (Aloini et al, 2022). Industry 4.0 is said to be a new phase of industrial change by integrating technology as a solution offered for traditional businesses.…”
Section: Information Technologymentioning
confidence: 91%
“…Zamani et al (2022) mentioned that the appropriate applications of information technology provide guarantees in achieving the goals that have been set. The results of the study showed that technology is compatible with today's developing business concepts (Aloini et al, 2022). Industry 4.0 is said to be a new phase of industrial change by integrating technology as a solution offered for traditional businesses.…”
Section: Information Technologymentioning
confidence: 91%
“…The implementation of digitalisation creates considerable potential from a strategic, operational and financial perspective (Aloini, et al, 2022;Brunetti, et al, 2020;Müller, 2019). Fragmented implementation concepts in the (stationary) medical supply store lead to key competitive disadvantages compared to those players who operationalise digitalisation holistically.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The focus of this paper is on digital transformation, but it should be emphasised that the medical supply store is simultaneously affected by other constraints or crossindustry trends. The named circumstances can only be remedied in a fragmented way by strategy concepts (Aloini, et al, 2022;Deckert & Wohllebe, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The concept presented in this study refers to a business model that leads to public needs so that Research and Development expenditures, wellbeing, sustainable cities and communities, and adoption of emerging technologies can improve the business model implemented by institutions engaged in research and development (Agostini et al, 2020;Latronico and Pellegrini, 2019). Indeed, this cannot be separated from existing resources that must be optimized and increased.…”
Section: Introductionmentioning
confidence: 99%